Tingkat Pendapatan Masyarakat Pesisir dalam Pemanfaatan Dana Ekonomi Produktif (DEP) - Parmi, Handri Jurya (Business Management, 2022)
Research aims to study the effect of the use of productive economic funds (PEF) in the coastal community (fishermen, traders and processors) empowerment program on coastal communities’ income level in Mataram Township. Based on simple regression analysis, it was obtained the value of the correlation coefficient (r) of 0.475. That means there was a fairly strong relationship between the PEF-income coastal community (fishermen, traders and processors). In general, PEF affect on the level of coastal community income (fishermen, traders and processors) by 22.55%, while another 77.45% was influenced by other variables or factors. It can also be determined that the regression pattern between the PEF and a total income of fishermen, traders and processors was Y = 723,076.2 + 0.503 (x), meaning: each additional amount of IDR PEF of 1, will increase the amount of income of fishermen, traders and processors by IDR 0.503. PEF or any increase of 1% will increase the amount of income of fishermen, traders and processors by 0.503%. It can be concluded that the use of PEF in the Coastal Community Economic Empowerment Program has a significant influence on increasing income coastal community (fishermen, traders, and processors).